Estrategias de calidad para la gestión operativa de agencias de viajes minoristas” - Aguilar Castro Nadia Nahomi (2024)
The research aims to design and apply quality strategies for the operational management of retail travel agencies in order to guarantee customer satisfaction and competitiveness. The study used an exploratory research methodology, with a qualitative approach, including interviews and observation, with specific objectives of continuous improvement. The results indicated that the application of ISO 9001 standards, clear work systems and employee incentives optimize communication, response time and services provided by retail travel agencies. The recommendation includes adopting a customer-based approach, strengthening employee training and investing in technology. The conclusion of the study highlights the importance of managing quality and continually improving services for retail travel agencies to remain competitive.